Malignancy prediction of cutaneous and subcutaneous neoplasms in canines using B-mode ultrasonography, Doppler, and ARFI elastography - da Cruz, Igor Cezar Kniphoff [UNESP]; Carneiro, Rafael Kretzer [UNESP]; de Nardi, Andrigo Barboza [UNESP]; Uscategui, Ricardo Andrés Ramirez; Bortoluzzi, Eduarda Mazzardo; Feliciano, Marcus Antônio Rossi [UNESP] (Springer Nature, 2022)
Background: Cutaneous and subcutaneous neoplasms are highly prevalent in dogs, ranging from benign to highly aggressive and metastatic lesions. The diagnosis is obtained through histopathology, however it is an invasive technique that may take a long time to obtain the result, delaying the beginning of the adequate treatment. Thus, there is a need for non-invasive tests that can help in the early diagnosis of this type of cancer. The aim of this study was to verify the accuracy of B-mode ultrasonography, Doppler, and ARFI elastography to predict malignancy in cutaneous and subcutaneous canine neoplasms. In addition, we aim to propose an ultrasonography evaluation protocol and perform the neoplasms characterization using these three proposed techniques. Results: Twenty-one types of specific neoplasm were diagnosed, and using B-mode, we verified the association between heterogeneous echotexture, invasiveness, presence of hyperechoic spots, and cavity areas with malignancy. An increased pulsatility was verified in malignant neoplasms using Doppler (cut-off value > 0.93). When using the elastography, malignancy was associated with non-deformable tissues and shear wave velocity > 3.52 m/s. Evaluation protocols were proposed associating 4, 5, 6, or 7 malignancy predictive characteristics, and characterization was done for all tumors with at least two cases. Conclusions: We concluded that ultrasonography methods are promising and effective in predicting malignancy in these types of tumors, and the association of methods can increase the specificity of the results.
Keywords: Cancer; Canine; Oncology; Ultrasonography